Prenatal co-exposure to manganese and depression and 24-months neurodevelopment - Rocha, Teresa Verenice Muñoz (Neurotoxicology, 2017)
BACKGROUND: Normal prenatal neurodevelopment follows stages that are potentially influenced by both chemical and psychosocial environments. Exposure to elevated manganese during this critically vulnerable period has been found to be neurotoxic. Independently, maternal prenatal depression has been associated with subsequent neurodevelopmental decrements in children. The association between child neurodevelopment and prenatal co-exposure to manganese and maternal depression has not been sufficiently studied. METHODS: During pregnancy and at birth, we measured maternal blood and cord blood manganese levels respectively. Maternal depression was assessed in the 3(rd) trimester of pregnancy using the Edinburgh Depression Scale. Neurodevelopment was evaluated at 24 months of age with the Bayley Scales of Infant Development. A multivariate multiple regression model was used to analyze cognitive, language and motor scores simultaneously for 473 children from the PROGRESS birth cohort in Mexico City. RESULTS: Over 25% of our study participants reported having depressive symptoms. 3(rd) trimester blood manganese as well as depressive symptoms were independently negatively associated with all neurodevelopment scores in adjusted models. In stratified analyses, the negative association between manganese (maternal as well as cord blood) and 24-month language scores was stronger among women with depressive symptoms. Receptive language was mostly affected. Inverted U-shaped curves were seen for the association between with cord blood manganese and neurodevelopment scores. CONCLUSIONS: Our findings are in line with previous studies of manganese and depression neurotoxicity. The prenatal period may be particularly sensitive to manganese and depression co-exposures and should be of interest for public health interventions to promote healthy emotional and nutritional pregnancies.